If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2cos(3x + 1) Reorder the terms: y = 2cos(1 + 3x) y = (1 * 2cos + 3x * 2cos) y = (2cos + 6cosx) Solving y = 2cos + 6cosx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2cos + 6cosx
| -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t | | 15=-6n+3n | | -7r=-21 | | p+6=2 | | x^4-49x^2-360=0 | | y-8=4x | | a^3+b^2=72 | | y=(3m+2n)(6m-8n) | | 2.3x-0.4=15.7 | | (3x)x=48 | | X*-6x+5=0 | | -68=-5x-8 | | x^2+v^2=y | | 5=25t+10 | | 21=-9 | | 21=9 | | 5y+x=w | | y=-sin(3.14x+1)-2 | | -4+8V=6+3v | | X^2(x-3)=320 | | y=(5x-3)(2x+1) | | -6(4d+10)+7d=-3d | | 202=(4x-1)*(5x+3) | | 3(n-3)-(7-n)= | | 50.4=2.5x*(15.4+y) | | 12=7t-44 | | x+2/8=-3 | | 50.4=2.5x*(15.4+x)y |